2003
DOI: 10.1023/a:1024707326943
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The present investigation was undertaken to study the effect of chronic treatment with angiotensin (AT1) receptor antagonist losartan (2 mg/kg, p.o., 6 weeks) on streptozotocin (STZ) induced (45 mg/kg, i.v., single dose) renal dysfunctions in diabetic rats. Injection of streptozotocin produced not only the cardinal symptoms of diabetes mellitus like loss of body weight, hyperglycemia, and hypoinsulinemia but also the renal dysfunctions. Losartan treatment significantly prevented all these changes except STZ-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Hence, to prevent progression of diabetic nephropathy, systemic and glomerular pressures must be controlled using angiotensin-converting enzyme inhibitors (ACEIs), angiotensin I receptor blockers (ARBs), etc. Many studies have demonstrated the efficacy of ACEIs and ARBs on nephropathy models, including a model of diabetic nephropathy [9, 10]. In addition, recent clinical studies of ACEIs [11] and ARBs [12, 13] have revealed that these agents exhibit renoprotective effects, including preventing the progression of nephropathy with reducing urine protein.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, to prevent progression of diabetic nephropathy, systemic and glomerular pressures must be controlled using angiotensin-converting enzyme inhibitors (ACEIs), angiotensin I receptor blockers (ARBs), etc. Many studies have demonstrated the efficacy of ACEIs and ARBs on nephropathy models, including a model of diabetic nephropathy [9, 10]. In addition, recent clinical studies of ACEIs [11] and ARBs [12, 13] have revealed that these agents exhibit renoprotective effects, including preventing the progression of nephropathy with reducing urine protein.…”
Section: Introductionmentioning
confidence: 99%